Accelerated Chemical Thermodynamics of Uranium Extraction from Seawater by Plant‐Mimetic Transpiration. Issue 24 (28th October 2021) - Wang, Ning; Zhao, Xuemei; Wang, Jiawen; Yan, Bingjie; Wen, Shunxi; Zhang, Jiacheng; Lin, Ke; Wang, Hui; Liu, Tao; Liu, Zhenzhong; Ma, Chunxin; Li, Jianbao; et al.
Abstract: The extraction of uranium from seawater, which is an abundant resource, has attracted considerable attention as a viable form of energy‐resource acquisition. The two critical factors for boosting the chemical thermodynamics of uranium extraction from seawater are the availability of sufficient amounts of uranyl ions for supply to adsorbents and increased interaction temperatures. However, current approaches only rely on the free diffusion of uranyl ions from seawater to the functional groups within adsorbents, which largely limits the uranium extraction capacity. Herein, inspired by the mechanism of plant transpiration, a plant‐mimetic directional‐channel poly(amidoxime) (DC‐PAO) hydrogel is designed to enhance the uranium extraction efficiency via the active pumping of uranyl ions into the adsorbent. Compared with the original PAO hydrogel without plant‐mimetic transpiration, the uranium extraction capacity of the DC‐PAO hydrogel increases by 79.33% in natural seawater and affords the fastest reported uranium extraction average rate of 0.917 mg g −1 d −1 among the most state‐of‐the‐art amidoxime group‐based adsorbents, along with a high adsorption capacity of 6.42 mg g −1 within 7 d. The results indicate that the proposed method can enhance the efficiency of solar‐transpiration‐based uranium extraction from seawater, particularly in terms of reducing costs and saving processing time. Abstract : A plant‐mimetic directional‐channel hydrogel is designed for transpiration‐enhanced uranium extraction from seawater. Attributing to the transpiration boosted seawater transport and the raise of the temperature, the chemical thermodynamics for uranium adsorption is enhanced and the uranium extraction capacity is increased by 79.33%.